Bibliometric analysis of velocity and acceleration objects in rectilinear motion - Adi Pramuda; Septian Setiawan; Soka Hadiati (Institute of Computer Science (IOCS), 2026)
The development of velocity and acceleration teaching aids for linear motion has attracted increasing attention due to the growing integration of digital technologies in physics education. However, a comprehensive bibliometric mapping of this research field remains unavailable. Therefore, this study aims to analyze publication trends, thematic structures, and emerging research directions related to velocity and acceleration teaching aids in linear motion physics. This study employed a quantitative bibliometric approach. A total of 376 journal articles published between 2019 and 2024 were retrieved from the Google Scholar database through Harzing's Publish or Perish software. The data were analyzed using Microsoft Excel for publication trend analysis and VOSviewer for co-occurrence, network, overlay, and density visualizations. The results revealed that publication output increased substantially during the study period, reaching its peak in 2023 with 94 publications (25%). Co-occurrence analysis identified five major thematic clusters, including teaching aids, Arduino-based experimentation, linear motion concepts, acceleration, and velocity measurement. Overlay visualization indicated that Arduino, acceleration analysis, and digital experimentation emerged as recent research trends. Density visualization showed that motion, velocity, and acceleration remain the most established research themes. This study contributes a comprehensive bibliometric mapping of velocity and acceleration teaching-aid research, highlighting emerging opportunities for IoT-integrated laboratories, sensor-based experimentation, remote laboratories, and AI-assisted physics learning. The findings provide a strategic reference for researchers and educators in developing future digital physics laboratory innovations.